Impulsiveness as a moderator of amphetamine treatment response for cocaine use disorder among ADHD patients. (1st August 2020) - Blevins, Derek; Choi, C. Jean; Pavlicova, Martina; Martinez, Diana; Mariani, John J.; Grabowski, John; Levin, Frances R.
Highlights: Impulsiveness is a key feature of both cocaine use disorder (CUD) and ADHD. Amphetamines are a highly effective treatment for ADHD and have evidence for CUD. Amphetamines were found to improve both ADHD and CUD symptoms in a comorbid sample. CUD improvement in this sample was significantly moderated by trait impulsiveness. Abstract: Background: Amphetamines are a first-line treatment for ADHD and have shown promise for the treatment of cocaine use disorder (CUD), both alone and with comorbid ADHD. Impulsiveness is a key aspect of both ADHD and substance use disorders. We sought to understand the role of baseline impulsiveness in the treatment of comorbid CUD and ADHD. Methods: In a post hoc analysis ( N = 76) of a 14-week, double-blind, randomized, placebo-controlled trial of mixed amphetamine salts-extended release (MAS-ER) for comorbid ADHD and CUD, we examined the relationship between treatment response and participants' baseline Barratt Impulsiveness Scale (BIS-11) score by comparing those with scores below versus above the median. In the original trial, participants received daily 60 mg MAS-ER, 80 mg MAS-ER, or placebo, in conjunction with cognitive behavioral therapy. Results: The odds of a cocaine-abstinent week over time were significantly greater in the high BIS group compared to the low BIS group, both when missing data was treated as missing ( p = .0155; OR = 1.23, 95% CI: 1.13, 1.35 versus OR = 1.04, 95% CI: 0.95, 1.15) and when missing data was treated as cocaine-positive ( p = .003; OR = 1.15, 95% CI: 1.06, 1.24 versus OR = 0.96, 95% CI: 0.88, 1.05). Conclusions: The results show an association between higher within-group trait impulsiveness, as measured by the BIS-11, and response to MAS-ER for CUD in a cohort with comorbid ADHD. This result further demonstrates that impulsiveness is an important factor when considering treatment options for patients with CUD and that higher baseline impulsiveness may predict response to treatment with psychostimulants for CUD.